Elvis : The Illustrated Biography - Clayton, Marie (UK Trans Atlantic Press, 2008)
This title charts the life and achievements of Elvis, the boy from Tupelo, Mississippi, from his first taste of fame in the early 1950s to his untimely death in 1977.
Include Color Illustrations
Keywords: Rock musicians -- Biography